Pengaruh Blansir Terhadap Karakteristik Fisikokimia Daun Leilem (Clerodendrum Minahassae Teisjm. & Binn) - Gloria Kusmin; Maria F. Sumual; Lana E. Lalujan (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2023)
Leilem leaves are vegetables that have a short shelf life, so they require postharvest handling to maintain the quality and quantity of leilem leaves. Blanching can be done as an effort to handle postharvest vegetables which can extend the shelf life of vegetables by heating methods. This research was conducted to determine the effect of blanching time on the quality and nutritional value of leilem leaves. The study was based on the RAL method with 5 treatments namely K0 (without blanching), K1 (1 minute blanching), K2 (3 min blanching), K3 (5 min blanching), K4 (7 min blanching) at 85°C which included a test color (hunter method), water content (AOAC method), chlorophyll content (Wintermans & de Mots method), vitamin C content and antioxidant activity using the spectrophotometer method. The results showed that there was an effect of the dip blanching treatment on vegetable color, chlorophyll levels, vitamin C levels and antioxidant activity. Blanching at 85°C for 3 minutes increased the water content, chlorophyll content and antioxidant activity, but not vitamin C. A longer blanching time of more than 3 minutes could cause degradation and decomposition of the chlorophyll content and antioxidant activity of leilem leaves. Keywords: Blanching, Leilem leaves, Color, Chlorphyl, Vitamin C, Antioxidants and Moisture Content